(untitled) (MAUSAM, 1988)
In this paper diurnal variation of visibility during the months of November to February over Delhi airport has been studied by working out (i) Mean hourly values of visibility, (ii) Mean hourly frequencies of visibility and RVR of different ranges, The study suggests that lowest values of visibility (maximum frequencies of visibility and R VR of different ranges) occur around 0200 GMT, The incidence rapidly decreases after 0400 GMT. It is also observed that generally there is another minimum (maximum for frequencies) around 1600 GMT which is, however, not well defined.